2012
DOI: 10.1142/s1402925112400104
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Traveling Water Waves of Moderate Amplitude

Abstract: We prove the existence of solitary traveling wave solutions for an equation describing the evolution of the free surface for waves of moderate amplitude in the shallow water regime. This nonlinear third-order partial differential equation arises as an approximation of the Euler equations, modeling the unidirectional propagation of surface water waves. We give a description of the solitary wave profiles by performing a phase plane analysis and study some qualitative features of the solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…[2,6], it is not apparent how to control the solutions of (1) globally, due to the fact that this equation involves higher order nonlinearities in u and its derivatives than the CH equation. On the other hand, if one passes to a moving frame, it can be shown that there exist solitary travelling wave solutions decaying at infinity [14]. Their orbital stability has been recently studied in [9] using an approach proposed by Grillakis, Shatah and Strauss [15], which takes advantage of the Hamiltonian structure of (1).…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…[2,6], it is not apparent how to control the solutions of (1) globally, due to the fact that this equation involves higher order nonlinearities in u and its derivatives than the CH equation. On the other hand, if one passes to a moving frame, it can be shown that there exist solitary travelling wave solutions decaying at infinity [14]. Their orbital stability has been recently studied in [9] using an approach proposed by Grillakis, Shatah and Strauss [15], which takes advantage of the Hamiltonian structure of (1).…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…which was first derived by Johnson [12], whose considerations were extended by Constantin and Lannes [4]. We refer to [11] for a first study of smooth solitary waves and to [10] for a more extensive characterization of TWS of equation (15). We introduce the traveling wave Ansatz u(x, t) = u(x − c t) and integrate once to obtain…”
Section: Surface Waves Of Moderate Amplitude In Shallow Watermentioning
confidence: 99%
“…For a wellposedness result in the context of Besov spaces we refer the reader to [25], whereas a result on low regularity solutions with 1 < s ≤ 3/2 may be found in [22], and for global conservative solutions and continuation of solutions beyond wave breaking we point out [29]. The equation admits smooth as well as cusped and peaked solitary and periodic traveling wave solutions, and also solitary traveling waves with compact support [14,15,16]. Furthermore, the smooth solitary traveling wave solutions are known to be orbitally stable [10].…”
Section: Introductionmentioning
confidence: 99%